2015
DOI: 10.3390/ijerph121215001
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Excessive Sodium Intake and Smoking and Alcohol Intake Among Korean Men: KNHANES V

Abstract: In this study, we evaluated the associations of smoking and alcohol intake, both independently and collectively, with sodium intake in Korean men. Subjects (6340 men) were from the fifth Korean National Health Examination Survey (2010–2012). Smoking-related factors included smoking status, urinary cotinine level, and pack-years of smoking. Food intake was assessed using a 24-h recall. The odds of excessive sodium intake were estimated using survey logistic regression analysis. The smoking rate was 44.1%. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…However, participants who reported alcohol use presented higher salt intake, as seen in almost all assessment measures, reproducing previous findings (44) . The hypotheses proposed to explain this relationship are related to alcohol consumption influencing salt enjoyment and to the fact that alcoholic beverages and salty foods frequently go together (45)(46)(47) .…”
Section: Discussionmentioning
confidence: 99%
“…However, participants who reported alcohol use presented higher salt intake, as seen in almost all assessment measures, reproducing previous findings (44) . The hypotheses proposed to explain this relationship are related to alcohol consumption influencing salt enjoyment and to the fact that alcoholic beverages and salty foods frequently go together (45)(46)(47) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that smokers may have a higher energy intake, consume less fruit and vegetables, and adopt poorer dietary habits when compared with non-smokers [38,39]. Furthermore, smoking might influence the preference for salt [40,41]. Thus, diet may confound the BP-smoking association.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…Another potential explanation may be that unhealthy lifestyle factors (smoking and alcohol intake) in the male populations is high [53, 54]. Choi et al found that simultaneous exposure to smoking and alcohol was associated with increased odds of excessive sodium intake [53].…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al found that simultaneous exposure to smoking and alcohol was associated with increased odds of excessive sodium intake [53]. In the Korean society, males are more likely to engage in both smoking and alcohol consumption, which might affect the sodium intake.…”
Section: Discussionmentioning
confidence: 99%